2008
DOI: 10.1088/0953-4075/41/14/145502
|View full text |Cite
|
Sign up to set email alerts
|

A direct approach to the electromagnetic Casimir energy in a rectangular waveguide

Abstract: In this paper we compute the leading order Casimir energy for the electromagnetic field (EM) in an open ended perfectly conducting rectangular waveguide in three spatial dimensions by a direct approach. For this purpose we first obtain the second quantized expression for the EM field with boundary conditions which would be appropriate for a waveguide. We then obtain the Casimir energy by two different procedures. Our main approach does not contain any analytic continuation techniques. The second approach invo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…The calculation presented in Appendix C proves that the outer waveguides and their remaining boundaries do not affect the Casimir energy of the original waveguide (Region A1). It should be noted that a similar proof to this one was made previously for calculating the electromagnetic Casimir energy inside a conducting rectangular waveguide and the same results were obtained (see Appendix B in [31]). In this study, by applying the second sets of configurations shown in Fig. (2) and the mentioned renormalization program, the zero-and first-order radiative corrections were computed on the Casimir energy for the massive scalar field in φ 4 theory with Dirichlet boundary condition in an open-ended rectangular waveguide.…”
Section: Introductionsupporting
confidence: 75%
“…The calculation presented in Appendix C proves that the outer waveguides and their remaining boundaries do not affect the Casimir energy of the original waveguide (Region A1). It should be noted that a similar proof to this one was made previously for calculating the electromagnetic Casimir energy inside a conducting rectangular waveguide and the same results were obtained (see Appendix B in [31]). In this study, by applying the second sets of configurations shown in Fig. (2) and the mentioned renormalization program, the zero-and first-order radiative corrections were computed on the Casimir energy for the massive scalar field in φ 4 theory with Dirichlet boundary condition in an open-ended rectangular waveguide.…”
Section: Introductionsupporting
confidence: 75%
“…This method was first used by T.H. Boyer for the calculation of the Casimir energy for an electromagnetic field confined in a 3D conducting sphere [26] and it was named Box Subtraction Scheme (BSS) in the later works [27,28]. Up to now, in order to reduce possible ambiguities appearing in the calculation of the Casimir energy, multiple studies used this method [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Later, in order to reduce the ambiguities in the removal of divergences, this method was remarkably used in other studies [50][51][52]. This technique was also performed to calculate the first order radiative correction to the Casimir energy between two parallel plates for massive scalar field in φ 4 theory in one, two and three spatial dimensions [20,23].…”
Section: Introductionmentioning
confidence: 99%